Information literacy literature in the social sciences and humanities: a bibliometric study. Issue 1 (9th January 2017) - Bhardwaj, Raj Kumar
Abstract : Purpose: This paper aims to map information literacy literature in social sciences and humanities published during the period of 2001-2012. Design/methodology/approach: The data for the study are obtained from Scopus, accessible atwww.scopus.com . Study used the Transformative Activity Index (TAI) and relative citation impact (RCI) to know the impact of most productive countries and prolific institutions. The SCImago Journal and Country Rank accessible atwww.scimagojr.com/ was used to determine the SCImago Journal Rank and source normalized impact per paper. Findings: The study found that 1990 documents originating from 79 countries were published in this study area. These papers are published in 160 journals with an average ∼12.51 papers per journal. These papers have been cited 10, 025 times with ∼5.0. average citations per publication. Study also found that information literacy literature is published in 16 languages and the majority of the papers are in English, 1, 879 (94.4 per cent). The highest growth of publications (106.7 per cent) was found in 2005. The USA contributed the highest number, 1, 035 (52 per cent) papers. Moreover, of the 15 most productive countries, three recorded TAIs >100, and 12 countries recorded TAIs <100. In all, 160 institutions worldwide have contributed in information literacy research. Study also found that maximum literature published on the subject by a single author is 828 (41.6 per cent). Universidad de Granada, Granada, Spain has produced the highest number of papers (24, or 1.2 per cent) and received 61 (0.6 per cent) citations, while University of Strathclyde has the highest RCI (∼2.7) for its publications. Pintos, María from Universidad de Granada has published the maximum number of papers (18) that have been cited 78 times. Social implications: The study endeavors to showcase information literacy research outcomes in social sciences and humanities. It involves quantitative analysis of the literature in this domain using bibliographic elements such as keywords, authors, affiliation, publication and citations. Originality/value: No study has been conducted so far to map the information literacy literature in social sciences and humanities. Study will be useful in understanding the progress on information literacy in the area of social sciences and humanities. The study is significant for social scientists to foster further research in this emerging area.